2019
DOI: 10.3390/biom10010055
|View full text |Cite
|
Sign up to set email alerts
|

Decreased H19, GAS5, and linc0597 Expression and Association Analysis of Related Gene Polymorphisms in Rheumatoid Arthritis

Abstract: Long noncoding RNAs (lncRNAs) widely participate in human diseases by regulating gene transcription, modulating protein function, or acting as ceRNAs. Yet, their roles in rheumatoid arthritis (RA) remain obscure. In this study, the expression of three lncRNAs (H19, GAS5, and linc0597) in peripheral blood mononuclear cells (PBMCs) were detected in 77 RA patients and 78 controls using quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR). The association of lncRNAs related gene polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 55 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…rs6790 was associated with the risk of RA in the recessive model. Wu et al (34) reported that the genotype frequencies of the rs6790 SNP of lncRNA GAS5 gene was significantly associated with the risk of RA, but they did not reveal the relation of this SNP with RA risk with dominant and recessive patterns. Thus, further studies are required to explain the specific role of lncRNA GAS5 and its polymorphisms in RA development.…”
Section: Discussionmentioning
confidence: 96%
“…rs6790 was associated with the risk of RA in the recessive model. Wu et al (34) reported that the genotype frequencies of the rs6790 SNP of lncRNA GAS5 gene was significantly associated with the risk of RA, but they did not reveal the relation of this SNP with RA risk with dominant and recessive patterns. Thus, further studies are required to explain the specific role of lncRNA GAS5 and its polymorphisms in RA development.…”
Section: Discussionmentioning
confidence: 96%
“…For several years, LncRNA‐GAS5 was regarded as a tumour suppressor gene. However, recent studies have shown that LncRNA‐GAS5 plays a role in the pathogenesis of immune‐mediated inflammatory diseases, such as SLE, multiple sclerosis, rheumatoid arthritis, inflammatory bowel disease and immune thrombocytopenia 16,37‐40 . To date, there are no reports indicating an association between LncRNA‐GAS5 gene polymorphism and the risk for SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have linked this lncRNA to other inflammatory and autoimmune conditions [21–24]. For instance, increased H19 levels were observed in synovial tissue from rheumatoid arthritis and knee cartilage from osteoarthritis patients compared to controls, as well as muscle biopsies from inclusion body and anti‐Jo‐1‐associated myositis patients compared to controls [21–23]. Proposed mechanisms include regulation of H19 expression by stress and inflammatory signals, while H19 in turn regulates expression of a number of downstream targets via little‐understood mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been proposed that lncRNAs may serve as competing endogenous RNAs capable of blocking and inhibiting micro-RNAs via complementary base pairing [20]. Previous studies have linked this lncRNA to other inflammatory and autoimmune conditions [21][22][23][24]. For instance, increased H19 levels were observed in synovial tissue from rheumatoid arthritis and knee cartilage from osteoarthritis patients compared to controls, as well as muscle biopsies from inclusion body and anti-Jo-1-associated myositis patients compared to controls [21][22][23].…”
Section: Discussionmentioning
confidence: 99%